Implementasi strategi public relations terhadap konsumen pada toko sembako dalam meningkatkan penjualan - Maulidiya, Zuni (Maliki Interdisciplinary Journal, 2024)
Public relations strategy plays an important role in the marketing process of a product to consumers. produce an increase in the number of sales. This research focuses on and aims to determine the implementation of public relations strategies towards consumers in grocery stores to increase sales. This research is descriptive-qualitative in nature and was obtained from data collection carried out by going directly to the field and interviewing shop owners. The results of this research show that the Azzahara grocery store shows a commitment to providing good public services and building strong relationships with their customers.